P007 Identification and characterisation of intestine-derived circulating resident memory T cells (ex-Trm) in health and Inflammatory Bowel Disease. (27th May 2021) - Rodger, B; Hoti, I; Gordon, H; Lindsay, J; Stagg, A
Abstract: Background: Tissue resident memory T cells (Trm) persist in peripheral tissues where they protect against pathogens but can also contribute to inflammatory disease. Recent work shows that Trm can re-enter the circulation and give rise to new effector T cell and Trm populations in secondary tissue sites. Such 'ex -Trm' derived from the skin co-express the residency marker CD103 with cutaneous leukocyte antigen (CLA), a marker associated with skin tropism. Many T cells in the human intestine are Trm but it is unknown whether these cells re-enter the circulation; the existence of gut-derived ex-Trm would have important implications for IBD treatment targeting the recruitment of circulating gut-homing cells. Here, we identify a population of blood cells that co-express CD103 and the gut-homing integrin a4b7 and determine how they are changed in IBD. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from healthy volunteers and patients with active IBD (Crohn's disease or ulcerative colitis). Cell surface staining and multi-colour flow cytometry were used to identify CD4+ and CD8+ subsets of antigen experienced (CD45RA-) conventional T cells (abTCR+) and determine expression of markers associated with tissue tropism and residency. Results: Staining with antibodies to CD103 and b7 integrin were used to define CD103b7+a4b7+ putative gut ex-Trm based on the excess per cell expression of b7 resulting from its contribution to both integrins. A separate CD103b7+a4b7- population defined by 1:1 expression of CD103 and b7 contained CLA+ skin ex-Trm. Gut ex-Trm comprised 0.3% total circulating CD8 + T cells (range 0.02–1.4%), and 1.2% CD4 + T cells (range 0.3–3%). Gut and skin ex-Trm were phenotypically similar; both expressed the residency associated markers CD101 and CD9 but lacked expression of CD69. Gut ex-Trm were phenotypically distinct from both traditional CD103-a4b7+ gut tropic CD45RA- antigen-experienced T cells and naïve T cells; significantly more gut ex-Trm expressed CD101 and CD9 and fewer expressed CD27. The proportion of gut ex-Trm did not differ between heath and IBD. However, the ratio of gut:skin ex Trm was significantly reduced in active Crohn's disease but not ulcerative colitis indicating a selective reduction in the population derived from the intestine. Conclusion: A putative population of gut-derived ex-Trm can be identified in the blood of healthy controls and IBD patients. This population has a distinctive phenotype similar to that of previously described skin-derived ex-Trm. Circulating ex-Trm could link discreet areas of intestinal inflammation in Crohn's disease and there is a selective loss of the gut ex-Trm population from the blood of these patients. The role of ex-Trm in IBD merits further study.